An Factors Associated with the Incidence of Hypertension Among the Elderly in the Working Area of Puskesmas Desa Lalang, Medan City, in 2025 - Devy Meilani br Ginting; Mindo Tua Siagian; Henny Arwina Bangun; Donal Nababan; Jasmen Manurung (JURNAL KESMAS DAN GIZI (JKG), 2025)
Hypertension in the elderly is associated with the aging process, as blood pressure tends to increase with age. Generally, hypertension in older adults is caused by changes in blood vessel conditions. This study aimed to analyze the factors associated with the incidence of hypertension among the elderly in the working area of Puskesmas Desa Lalang, Medan City. This research was a descriptive explanatory study conducted from July 2024 to January 2025. The sample consisted of 83 elderly individuals. Data analysis was performed using logistic regression tests. The Chi-square analysis revealed significant associations between hypertension and several factors: Body Mass Index (BMI) (p=0.000), family history of hypertension (p=0.000), smoking habits (p=0.017), consumption of high-salt and high-fat foods (p=0.000), and sleep pattern disturbances (p=0.000). The most dominant factor influencing the incidence of hypertension in the elderly was a family history of hypertension (p=0.001), with a B value of 4.809. It is recommended that families support the elderly by maintaining a healthy diet low in salt and fat, reducing or eliminating smoking habits, minimizing risk factors for hypertension, and accompanying them for regular health check-ups at the nearest health services